HMC / CeO2C2 composite material, preparation method and application of HMC / CeO2C2 composite material in lithium-sulfur battery

By synthesizing HMC/CeO2C2 composite materials, using its mesoporous carbon wall and oxygen-rich vacancies CeO2C2 nanoparticles, the problems of poor conductivity and shuttle effect of lithium-sulfur battery are solved, and a high energy density and long-life Li-S battery is achieved performance.

CN119153699AInactive Publication Date: 2024-12-17CHANGZHI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411295206.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-16
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The sulfur cathode of lithium sulfur batteries has poor electrical conductivity, easy structure deformability, lithium polysulfide is easily soluble in electrolyte and slow reaction kinetics, resulting in a decrease in energy density and shortened battery life. The existing carbon-based carriers are insufficient in suppressing the shuttle effect.

Method used

The HMC/CeO2C2 composite material was synthesized by hydrothermal method and annealing reduction method. Through the combination of mesoporous carbon spheres and oxygen-rich vacancies CeO2C2 nanoparticles, a sulfur-carrying material with high specific surface area and good conductivity was formed, which was used to prepare Li-S batteries. cathode.

Benefits of technology

High cycle stability and rate performance are achieved, and the capacity of 728mAh g-1 and discharge capacity of 741mAh g-1 are maintained after 500 cycles, and 3.18mAh cm-2 is provided under high surface sulfur loading and low electrolyte conditions. Area capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153699A_ABST
    Figure CN119153699A_ABST
Patent Text Reader

Abstract

The invention discloses an HMC / CeO2C2 composite material, a preparation method and application of the HMC / CeO2C2 composite material in a lithium-sulfur battery. The HMC / CeO2C2 composite material is successfully synthesized through a hydrothermal method and an annealing reduction method, and has multiple advantages that the large specific surface area and the mesoporous carbon wall are beneficial to permeation of sulfur and transmission of electrons / ions; rich mesopores and hollow inner cavities provide a structural basis for storing sulfur and buffering volume expansion of the sulfur; ceO2C2 nano-particles rich in oxygen vacancies grow in HMC in situ and are in close contact with carbon to form a CeO2C2 / C heterogeneous interface with good conductivity, and the CeO2C2 / C heterogeneous interface is used as an efficient catalyst and is beneficial to catalyzing the oxidation-reduction reaction of sulfur. The HMC / CeO2C2 composite material can be used as a multifunctional sulfur-loaded material with high sulfur loading, high conductivity and high catalytic activity, and an HMC / CeO2C2 / S electrode prepared by taking the HMC / CeO2C2 composite material as the sulfur-loaded material can be used for developing and preparing a cathode of a high-performance lithium-sulfur battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of materials and relates to the preparation and application of composite materials, and specifically relates to a HMC / CeO2C2 composite material, a preparation method and application in a lithium-sulfur battery. Background Art

[0002] With the rapid growth of the electric vehicle, renewable energy storage and portable electronic device markets, the demand for high energy density, low cost and environmentally friendly battery technology is becoming increasingly urgent. Lithium sulfur (Li-S) batteries have attracted much attention due to their main advantages of high energy density (theoretical specific capacity up to 2600Wh / kg), low cost raw materials (abundant sulfur reserves in the earth's crust) and environmental friendliness (no heavy metals). However, the commercialization process of Li-S batteries still faces many challenges, among which the technical bottlenecks faced by sulfur cathodes are as follows: (1) The conductivity of sulfur cathodes is poor, which requires the addition of conductive materials to improve, resulting in reduced energy density; (2) The large difference in density between sulfur and discharge products causes deformation or even collapse of the cathode structure, shortening the battery life; (3) The intermediate product lithium polysulfides (LiPSs) are easily soluble in the electrolyte, resulting in a shuttle effect, resulting in capacity decay and poor stability; (4) The reaction kinetics of the mutual conversion between LiPSs are sluggish, making it difficult to meet the requirements of fast charging and discharging.

[0003] Faced with the above technical bottlenecks, researchers have focused on innovating the structure and composition design of the sulfur cathode, aiming to significantly improve its conductivity and effectively curb the shuttling effect of polysulfides, thereby stabilizing the performance of the battery. Looking back at the early days of research on sulfur cathodes for lithium-sulfur batteries, researchers widely used advanced carbon materials such as porous carbon, hollow carbon, core-shell carbon, one-dimensional carbon nanotubes or carbon nanofibers, two-dimensional graphene, and three-dimensional MOF-derived carbon frameworks as carrier matrices for sulfur. These carbon materials significantly enhance the conductivity of the sulfur cathode due to their excellent conductivity, high specific surface area, and porous properties, and limit the dissolution of LiPSs through physical constraints. However, due to the limited physical constraints, the non-polar carbon matrix is ​​obviously ineffective in inhibiting the shuttling behavior of LiPSs, and the battery capacity is significantly attenuated during the charge and discharge process.

[0004] In recent years, in the process of in-depth exploration of Li-S battery performance optimization, the introduction of catalytically active polar compounds (metal oxides, sulfides, selenides, nitrides, phosphides and carbides) into carbon-based sulfur-supported materials is a widely used method. On the one hand, these compounds can construct a stable adsorption interface by virtue of their strong chemical affinity with LiPSs, thereby achieving effective anchoring of LiPSs. This chemical interaction not only limits the dissolution and free diffusion of LiPSs in the electrolyte, but also promotes the stable existence of LiPSs on the electrode surface, providing a rich reactant reserve for subsequent redox reactions. On the other hand, they can act as efficient catalysts, significantly reducing the energy barrier of the sulfur conversion process by optimizing the reaction path, accelerating the transfer of electrons and ions, and thus accelerating the redox reaction rate of sulfur. In summary, the synergistic effect of the dual mechanisms of adsorption and catalysis can effectively inhibit the shuttle effect and improve the overall performance of Li-S batteries. However, it is worth noting that although polar metal compounds have shown great potential in improving the performance of Li-S batteries, they also have some inherent limitations, such as insufficient conductivity, limited specific surface area, and insufficient catalytic active sites. These problems limit their effectiveness in practical applications. Therefore, exploring how to develop multifunctional sulfur-carrying materials by combining reasonable structural design with efficient catalysts is the key to solving the technical bottleneck of Li-S batteries.

[0005] In order to overcome the shortcomings of the prior art, the present invention is proposed. Summary of the invention

[0006] In order to overcome the shortcomings of the prior art, the first purpose of the present invention is to provide a HMC / CeO2C2 composite material, the second purpose is to provide a method for preparing the HMC / CeO2C2 composite material, and the third purpose is to provide an application of the HMC / CeO2C2 composite material in a Li-S battery.

[0007] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0008] A HMC / CeO2C2 composite material, the preparation method comprising the following steps:

[0009] Step S1, dispersing an appropriate amount of hollow mesoporous carbon spheres HMC and an appropriate amount of cerium nitrate in an appropriate amount of deionized water, adding an appropriate amount of NaOH, and performing ultrasonic treatment for an appropriate amount of time to make the dispersion uniform;

[0010] Step S2, transferring the uniformly dispersed mixture to a high-pressure reactor with a polytetrafluoroethylene liner, reacting at 95-105° C. for 9-11 hours, cooling naturally, collecting the precipitate by centrifugation, washing, and drying, and obtaining a HMC / CeO2 composite material.

[0011] Step S3, placing the HMC / CeO2 composite material in a tubular furnace, heating it to 480-520°C in a flowing 4-6% H2 / Ar atmosphere, maintaining it for 2.5-3.5 hours, and cooling it naturally to obtain the HMC / CeO2C2 composite material.

[0012] Preferably, step S2 is reacted at 100° C. for 10 h.

[0013] Preferably, in step S3, the temperature is raised to 500° C. at 5° C. / min and maintained for 3 h.

[0014] Preferably, the atmosphere in step S3 is a 5% H2 / Ar atmosphere.

[0015] Preferably, the preparation method of HMC comprises the following steps:

[0016] First, add an appropriate amount of ammonia water to a mixed solvent of ethanol / deionized water in a volume ratio of (6-8):1, add an appropriate amount of tetrapropyl orthosilicate under stirring, and when the solution presents a milky white colloid, add an appropriate amount of resorcinol and formaldehyde solution, and stir continuously;

[0017] Then, the precipitate was collected by centrifugation, washed several times with deionized water and ethanol, and dried under vacuum to obtain the HMC precursor;

[0018] Finally, the HMC precursor is placed in a tube furnace, carbonized at 680-720° C. for 2.5-3.5 hours in a flowing argon atmosphere, and naturally cooled; the carbonized product is then placed in a NaOH solution to etch the SiO2 template, centrifuged, washed, and dried to obtain the product.

[0019] More preferably, the carbonization condition of the HMC precursor is 700° C. for 3 h.

[0020] More preferably, the concentration of the NaOH solution for etching the SiO2 template is 4M.

[0021] The HMC / CeO2C2 composite material is used as a multifunctional sulfur-carrying material.

[0022] The HMC / CeO2C2 composite material is used as a sulfur-carrying material to prepare an HMC / CeO2C2 / S electrode.

[0023] The HMC / CeO2C2 / S electrode is used to prepare the cathode of a Li-S battery.

[0024] Beneficial effects:

[0025] The present invention successfully synthesized a HMC / CeO2C2 composite material by a hydrothermal method and an annealing reduction method. The composite material has multiple advantages: the large specific surface area and mesoporous carbon wall are conducive to the infiltration of sulfur and the transmission of electrons / ions; the abundant mesopores and hollow cavities provide a structural basis for storing sulfur and buffering its volume expansion; CeO2C2 nanoparticles rich in oxygen vacancies grow in situ in HMC and are in close contact with carbon to form a CeO2C2 / C heterogeneous interface with good conductivity as an efficient catalyst, which is conducive to catalyzing the redox reaction of sulfur. Based on the above advantages, the HMC / CeO2C2 composite material provided by the present invention, as a sulfur-carrying material, exhibits excellent cycle stability (728mAh g after 500 cycles). -1 The retention capacity) and rate performance (741mAh g -1 In addition, the HMC / CeO2C2 / S electrode exhibited a discharge capacity of 3.18 mAh cm-2 under high sulfur loading and low electrolyte conditions. -2 Therefore, the HMC / CeO2C2 composite material provided by the present invention can be used as a multifunctional sulfur-carrying material with high sulfur loading, high conductivity and high catalytic activity, and the HMC / CeO2C2 / S electrode prepared with the HMC / CeO2C2 composite material as the sulfur-carrying material can be used to develop and prepare the cathode of a high-performance Li-S battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Schematic diagram of the synthesis of HMC / CeO2C2 / S composite material.

[0027] Figure 2 (a) SEM images of HMC and (b,c) HMC / CeO2C2. (d) TEM images of HMC and (e) HMC / CeO2C2. (f) HRTEM image of HMC / CeO2C2. (g) IFFT images of CeO2C2 and (h) C in the marked areas of HMC / CeO2C2. (i) HAADF and EDS images of HMC / CeO2C2.

[0028] Figure 3 (a, b) XRD spectra, (c) EPR spectra and (d) Raman spectra.

[0029] Figure 4 N2 adsorption–desorption isotherms and pore size distribution of (a) HMC, (b) HMC / CeO2C2, and (c) HMC / CeO2C2 / S.

[0030] Figure 5 XPS spectra of (a) HMC / CeO2C2, (b) Ce3d, (c) O1s, and (d) C1s.

[0031] Figure 6 (a) Optical photos of different sulfur-carrying materials immersed in Li2S6 solution for 12 hours. (b) UV-visible absorption spectra of different sulfur-carrying materials after adsorption of Li2S6. XPS spectra of (c) Ce 3d and (d) O 1s on HMC / CeO2C2 before and after adsorption of Li2S6.

[0032] Figure 7 (a) Symmetrical cell at 1.0 mV s -1 CV curves of Li-S button cell at 0.1 mV s -1 CV curves and (c) peak current. (d-f) Enlarged images of the onset potentials of the C1, C2 and A1 peaks in Figure b and (gi) the corresponding Tafel plots.

[0033] Figure 8 CV curves of (a) HMC / CeO2C2 / S and (b) HMC / CeO2 / S at different scan rates. (c) I p and v 0.5 Linear fitting between. (e) EIS curve. (f) Z' and ω -1 / 2 The linear fit between .

[0034] Fig. 9 (a) Charge and discharge curves of different electrodes. (b) Details of the enlarged discharge curve. (c) Rate performance. (d) First charge and discharge curves of HMC / CeO2C2 / S and (e) HMC / CeO2 / S.

[0035] Fig.10 (a) Sulfur loading is 1.3 mg cm -2 and (b) 4.7 mg cm -2 Cycling performance of different electrodes at 0.5C. DETAILED DESCRIPTION

[0036] The essential contents of the present invention are described in detail below in conjunction with the embodiments, but the protection scope of the present invention is not limited thereto.

[0037] 1. Sample preparation, characterization and performance testing methods

[0038] 1. Preparation of HMC / CeO2C2 composite materials

[0039] Hollow mesoporous carbon spheres (HMC) were prepared according to the previous work of this research group. The preparation method is as follows: First, 3mL NH3·H2O (25wt%) was added to 80mL ethanol / deionized water solvent (volume ratio of 7:1), and 3.46mL tetrapropyl orthosilicate was added to the above mixed solution under magnetic stirring. When the solution was milky white colloid, 0.4g resorcinol and 0.56mL formaldehyde solution (37wt%) were added and stirred continuously at room temperature for 24h. Then, the precipitate was collected by centrifugation, washed several times with deionized water and ethanol, and vacuum dried at 50℃ to obtain HMC precursor. Finally, the HMC precursor was placed in a tube furnace, carbonized at 700℃ for 3h in a flowing argon atmosphere, and cooled naturally. The carbonized product was then placed in a 4M NaOH solution to etch the SiO2 template, and centrifuged, washed, and dried to obtain.

[0040] CeO2C2 nanoparticles (HMC / CeO2C2) composite materials with oxygen-rich vacancies embedded in hollow mesoporous carbon spheres were synthesized by hydrothermal and annealing processes using HMC as a carbon matrix and hexahydrated cerium nitrate as a cerium source. The specific preparation method includes the following steps:

[0041] Step S1, 80 mg of HMC and 0.4 mmol of cerium nitrate hexahydrate were ultrasonically dispersed in 80 mL of deionized water, and then 32 mg of NaOH was added and ultrasonicated for 30 minutes.

[0042] Step S2, transferring the uniformly dispersed mixture to a high-pressure reactor with a polytetrafluoroethylene liner, reacting at 100° C. for 10 hours, cooling naturally, collecting the precipitate by centrifugation, washing, and drying, and obtaining a HMC / CeO2 composite material.

[0043] Step S3, placing the HMC / CeO2 composite material in a tubular furnace, heating it to 500°C at 5°C / min in a flowing H2 / Ar (5%) atmosphere, maintaining it for 3 hours, and cooling it naturally to obtain the HMC / CeO2C2 composite material.

[0044] 2. Preparation of HMC / CeO2C2 / S samples

[0045] HMC / CeO2C2 / S was prepared by the usual melt diffusion method. First, sublimed sulfur and HMC / CeO2 were mixed and ground evenly in a mass ratio of 7:3. Then, the mixture was transferred to a high-pressure reactor, kept at 155°C for 12 hours, and cooled naturally to obtain HMC / CeO2C2 / S. For comparison, HMC / S and HMC / CeO2 / S samples were prepared using the same preparation method.

[0046] 3. Preparation and visual adsorption experiment of Li2S6

[0047] In a glove box filled with argon, sublimed sulfur and Li2S were dissolved in DOL / DME (i.e. dioxolane / dimethyl ether, volume ratio of 1:1) at a molar ratio of 5:1, and stirred continuously at 55°C for 12 hours to obtain 0.3mM Li2S6. Then, 2mg of HMC, HMC / CeO2 and HMC / CeO2C2 were added to a transparent glass bottle containing 2mL Li2S6 solution for visual adsorption test. The ultraviolet-visible spectrophotometer was used to qualitatively analyze the supernatant of Li2S6 after adsorption, and XPS was used to analyze the dried precipitate.

[0048] 4. Assembly and testing of symmetrical batteries

[0049] The sulfur-carrying materials (HMC, HMC / CeO2, HMC / CeO2C2) and the binder (PVDF) were uniformly dispersed in 2 mL of N-methylpyrrolidone (NMP) at a mass ratio of 4:1, then coated on aluminum foil and dried, and a disc with a diameter of 12 mm was punched out as the working electrode and counter electrode, Clegard 2400 polypropylene film was used as a diaphragm, and 40 μL of an electrolyte containing 0.3 M Li2S6 was added to assemble a CR2032 symmetrical battery. In addition, an electrolyte without Li2S6 was used as a control. The 10 mV·s -1 CV measurements were performed at a scan rate of .

[0050] 5. Preparation and assembly test of Li-S button battery cathode

[0051] The cathode sheet in the Li-S button cell is prepared as follows: First, the sulfur-carrying material (HMC, HMC / CeO2, HMC / CeO2C2), the conductive agent (Ketjen Black) and the binder (PVDF) are dispersed in NMP at a mass ratio of 8:1:1 to form a uniform slurry. Secondly, the slurry is evenly coated on aluminum foil, vacuum dried and flattened with a roller machine. Finally, a circular cathode sheet with a punching diameter of 12 mm is punched out using a tablet press.

[0052] The assembly process of Li-S button cell is as follows: the cathode sheet (HMC, HMC / CeO2, HMC / CeO2C2), the anode sheet (metal lithium sheet), the separator (Clegard 2400 polypropylene film), the electrolyte (containing 1wt% LiNO3 and 1mol·L -1 LiTFSI DOL / DME solution) was assembled into a CR2032 button cell. The area sulfur loading was 1.3 mg cm -2 , electrolyte / sulfur ratio (E / SμL·mg -1 ) is 15, and the area sulfur loading is 4.7 mg cm -2, E / S is 10. Constant current charge and discharge tests were performed on a NEWARE CT-4800T system with a current density of 0.1 to 4C and a voltage range of 1.7 to 2.8V. Cyclic voltammetry (CV) tests were performed on a MetrohmAutolab electrochemical workstation with a voltage range of 1.7 to 2.8V and a scan rate of 0.1mV·S -1 Electrochemical impedance spectroscopy (EIS) measurements were also performed on the MetrohmAutolab in the frequency range of 10 -2 Hz~10 5 Hz, and the voltage amplitude is 5mV.

[0053] 6. Characterization

[0054] The microstructure and structure of the samples were characterized by field emission scanning electron microscopy (FE-SEM, ZEISS Sigma 300) and high-resolution transmission electron microscopy (HR-TEM, FEI Talos F200x) equipped with energy dispersive x-ray spectrometer (EDS). The phase composition of the samples was confirmed by X-ray diffraction (XRD, Bruke, D8 Advance). The graphitization degree of the samples was analyzed by Raman spectroscopy (Horiba LabRAM HR Evolution). The chemical element composition and surface electronic state of the samples were analyzed by X-ray photoelectron spectroscopy (XPS, Thermo Scientific K-Alpha). The N2 adsorption-desorption isotherms and pore size distribution range of the samples were determined by a fully automatic specific surface and porosity analyzer (Micromeritics ASAP 2460). The amount of Ce element was determined by inductively coupled plasma optical emission spectroscopy (ICP-OES Agilent 5110). Ultraviolet-visible absorption spectroscopy (UV-Vis) was performed on a PerkinElmer LAMBDA 950 spectrometer, and electron paramagnetic resonance (EPR) was performed on a Bruker EMXplus spectrometer.

[0055] 2. Characterization and Performance Test Results

[0056] 1. Morphology and structure characterization

[0057] The synthesis process of HMC / CeO2C2 / S composites is as follows Figure 1As shown. First, tetrapropyl orthosilicate (TPOS) is rapidly hydrolyzed to form SiO2 primary particles, and resorcinol and formaldehyde are slowly polymerized to form resorcinol-formaldehyde oligomers (RF), which are self-assembled to form spherical HMC precursors with a core-shell structure (SiO2@SiO2 / RF). After high-temperature carbonization, the phenolic resin polymer is converted into an oxygen-containing carbon material. After etching with a NaOH solution, the SiO2 template is removed to obtain hollow carbon spheres with mesoporous carbon walls. Then, under ultrasonic conditions, Ce(NO3)3·6H2O and HMC are dispersed in deionized water, and Ce ions are adsorbed in the mesoporous carbon walls of HMC. NaOH is then added, and after hydrothermal treatment at 100°C, the mesoporous pores are used as nucleation sites, and CeO2 nanoparticles are generated by reaction with NaOH, obtaining a composite material (HMC / CeO2) in which CeO2 nanoparticles are embedded in the mesoporous pores of hollow carbon spheres. Next, annealing was performed in a H2 / Ar (5%) atmosphere to convert CeO2 into CeO2C2 nanoparticles with oxygen vacancies using HMC as the carbon source to obtain a composite material (HMC / CeO2C2). Finally, sulfur was infiltrated into HMC / CeO2C2 by melt diffusion technology to successfully prepare a sulfur-loaded composite material (HMC / CeO2C / S).

[0058] SEM and TEM were used to characterize the microstructure of the material. Figure 2 (a) shows that HMC presents a typical spherical morphology, and its particle size distribution is highly uniform, with a diameter range of 550-650nm, and the surface features are rough. TEM ( Figure 2 (d) further reveals the internal structure of HMC, clearly showing its hollow spherical morphology and clearly visible disordered open mesoporous channels. The cavity diameter is about 400nm and the wall thickness of the spherical shell is about 120nm. The internal cavity of HMC and the densely distributed mesoporous channels on the carbon wall are structural features formed after the in-situ generated SiO2 template is etched. This structure has the following advantages: on the one hand, the spacious internal cavity and porous carbon wall provide sufficient space for sulfur loading, effectively coping with the volume expansion of the sulfur reduction process; on the other hand, the open channels on the carbon wall can promote the penetration and diffusion of the electrolyte, and at the same time are beneficial to the subsequent melt sulfurization process. Subsequently, after hydrothermal and annealing processes, the SEM image ( Figure 2 (b, c) show that HMC / CeO2C2 still maintains a highly uniform spherical morphology, and the surface becomes rougher. TEM images show ( Figure 2 (e) CeO2C2 nanoparticles embedded in the carbon wall of HMC. HRTEM image of HMC / CeO2C2 Figure 2 In the example, the lattice fringes in the marked area are analyzed using the inverse fast Fourier transform (IFFT) and the fast Fourier transform (FFT). Figure 2In (g, h), the lattice fringe spacing in the red box is 0.322nm, which is consistent with the (111) crystal plane spacing (0.320nm) of CeO2C2 (PDF#44-0398); the lattice fringe spacing in the yellow box is 0.336nm, which is consistent with the (200) crystal plane spacing (0.335nm) of graphitic carbon. It is worth noting that we found that the FFT diffraction spots are blurred, the lattice fringe spacing of CeO2C2 is widened, and the lattice fringes are distorted, which is attributed to the formation of oxygen vacancies causing lattice stress changes. In addition, CeO2C2 / C is in close contact, and the disordered carbon in the vicinity of CeO2C2 nanoparticles is transformed into graphitized ordered carbon. This is because the presence of cerium ions during the annealing process promotes the graphitization of carbon materials. The structural characteristics of CeO2C2 are conducive to exposing more active sites on the one hand, and on the other hand, promote the transfer of electrons at the CeO2C2 / C interface. EDS image ( Figure 2 (i) shows the distribution of C, O and Ce elements in HMC / CeO2C2.

[0059] XRD is used to identify the phase of the material. Figure 3 As shown in a, all three materials have a bun-shaped peak near 2θ=24.5°, indicating that HMC belongs to an amorphous carbon structure. The XRD spectrum of HMC / CeO2C2 shows strong diffraction peaks at 2θ=24.4°, 25.2°, 27.9°, 44.1°, 45.2° and 51.1°, which are consistent with the (002), (110), (111), (300), (113) and (302) crystal planes of CeO2C2 (PDF44-0398), respectively. In addition, the characteristic diffraction peaks of HMC / CeO2 at 2θ=28.5°, 33.1°, 47.5° and 56.3° correspond to the (111), (200), (220) and (311) crystal planes of CeO2 (PDF34-0394), respectively. The width of the diffraction peak can reflect the microscopic information of grain size and crystal defects. Compared with CeO2, the characteristic diffraction peak of CeO2C2 is broadened. This is because the process of C atoms embedding into CeO2 to form CeO2C2 destroys the order of the crystal and produces a large number of oxygen vacancies. This is consistent with the analysis results of HRTEM. XRD spectrum of the sulfur-loaded sample ( Figure 3 (b) shows the characteristic peaks of typical S8 crystals, indicating that sulfur is successfully loaded in HMC, HMC / CeO2, and HMC / CeO2C2.

[0060] Electron paramagnetic resonance (EPR) was used to characterize the oxygen vacancies in the material. Figure 3In Figure c), the EPR spectra of HMC / CeO2 and HMC / CeO2C2 show characteristic signal peaks at g≈3503, which strongly confirms the existence of oxygen vacancies in the two materials. The EPR spectrum of HMC does not show obvious signals, proving that there are no oxygen vacancies in the material. Further comparative analysis shows that HMC / CeO2C2 shows stronger signal intensity than HMC / CeO2, revealing that the concentration of oxygen vacancies in HMC / CeO2C2 is higher. In the Raman spectrum ( Figure 3 In (d), all three materials show D band (~1340 cm) and G band (~1590 cm), where the D peak corresponds to defective / disordered carbon and the G peak corresponds to graphitized carbon. G / I D The higher the value, the higher the degree of ordered orientation of carbon, which is more conducive to the transmission of electrons. In contrast, HMC / CeO2C2 has the highest degree of order and the best conductivity.

[0061] The pore structure characteristics of the material were studied using N2 adsorption-desorption isotherms ( Figure 4 ac). HMC, HMC / CeO2C2 and HMC / CeO2C2 / S all show type IV isotherm characteristics. HMC and HMC / CeO2C2 show obvious hysteresis loops in the range of 0.45-0.80P / P0, indicating the presence of a mesoporous structure. The specific surface area, pore volume and pore size distribution of different materials are shown in Table 1. After CeO2C2 is embedded in the HMC material, the specific surface area and pore volume decrease, and the pore size distribution remains unchanged. This is because the density of the HMC / CeO2C2 composite material increases compared to the density of HMC, and the pore size is due to the etching of SiO2 particles. After HMC / CeO2C2 is loaded with sulfur, the hysteresis loop appears in a higher relative pressure range (0.68-0.96P / P0), and the specific surface area and pore volume drop sharply. This is because sulfur penetrates into the mesoporous pores of HMC / CeO2C2 during the melt diffusion process. The Ce content was accurately determined by ICP-OES. The Ce contents in HMC / CeO2 and HMC / CeO2C2 were 38.47wt% and 35.02wt%, respectively, indicating that the cerium contents of the two were basically the same.

[0062] Table 1 Porous characteristics of HMC, HMC / CeO2C2 and HMC / CeO2C2 / S

[0063]

[0064] XPS was used to analyze the surface chemistry of HMC / CeO2C2 composite materials. The full XPS spectrum of HMC / CeO2C2 ( Figure 5 (a) shows the coexistence of C, O, and Ce elements. The high-resolution XPS spectrum of Ce 3d ( Figure 5b) consists of two multipliers (v and u), representing Ce 3d 3 / 2 and Ce 3d 5 / 2 Two spin-orbit splitting, where Ce 3d 3 / 2 can be deconvoluted into four peaks (labeled v°, v', v", and v''); Ce 3d 5 / 2 It can also be deconvoluted into 4 peaks (labeled as u°, u', u", and u''). The three peak pairs of u° / v°, u'' / v'' and u''' / v'' are attributed to Ce. 4+ , the u' / v' pair of peaks is attributed to Ce 3+ 。 3+ The presence of once again confirms that oxygen vacancies are introduced into CeO2C2, resulting in charge imbalance. 4+ / Ce 3+ The charge transfer can promote the mutual transformation of polysulfides on the catalyst surface. The high-resolution XPS spectrum of O1s ( Figure 5 c) shows that the peaks at 529.2, 531.5 and 533.1 eV binding energies correspond to the (O α ), adsorbed oxygen (O β ) and combined oxygen (O γ ). Among them, the content of chemically adsorbed oxygen is 54.75wt%, which is the most active oxygen in the sulfur redox process. High-resolution XPS spectrum of C 1s ( Figure 5 (d) can be deconvoluted into three different binding states, namely CC / C=C (284.8 eV), CO (285.6 eV) and OC=O (289.0 eV).

[0065] 2. Analysis of adsorption catalytic performance

[0066] In order to evaluate the adsorption capacity of sulfur-supporting materials for polysulfide, the same mass of three sulfur-supporting materials were immersed in Li2S6 solution and left to stand for 12 h ( Figure 6 (a). Compared with the blank Li2S6 solution, the color of the Li2S6 solution containing HMC and HMC / CeO2 becomes lighter, and the color of the Li2S6 solution containing HMC / CeO2C2 is almost colorless. The supernatant was further measured by UV-Vis absorption spectrum ( Figure 6In b), the intensity order of the absorption peak of Li2S6 is HMC / CeO2C2 < HMC / CeO2 < HMC, indicating that the adsorption capacity is HMC / CeO2C2 > HMC / CeO2 > HMC. The adsorption of Li2S6 by HMC is due to the high specific surface area and rich mesoporous structure of HMC. In addition to the above reasons, for the adsorption of Li2S6 by HMC / CeO2C2, the CeO2C2 nanoparticles with rich oxygen vacancies embedded in HMC expose a large number of polar sites, which produce chemical adsorption with Li2S6, further enhancing the adsorption of polysulfides. To further study the chemical interaction between CeO2C2 and Li2S6, the XPS spectra of CeO2C2 before and after adsorbing Li2S6 were analyzed ( Figure 6 in c and d). After adsorbing Li2S6, the peak corresponding to Ce3d shifts towards lower binding energy, and the peak corresponding to O1s shifts towards higher binding energy, indicating that the electron cloud density around the Ce atom increases and the electron cloud density around the O atom decreases. This is because S 2- and Li + in lithium polysulfide interact with Ce 4+ / 3+ and O 2- respectively.

[0067] The cyclic voltammetry method was used to evaluate the effect of HMC / CeO2C2 on the kinetics of polysulfide redox reaction. The CV curves of the symmetric cell ( Figure 7 in a) show that there is no current response in the symmetric cell when the electrolyte does not contain Li2S6; when the electrolyte contains Li2S6, all three symmetric cells have current responses, indicating that the current originates from the redox process of Li2S6. The symmetric cell of HMC / CeO2C2 shows two reversible reduction peaks (I: S8 → Li2S6 and II: Li2S6 → Li2S) and two oxidation peaks (III: Li2S → Li2S6 and IV: Li2S6 → S8), with the largest current integration area and the smallest polarization. The redox peaks of the series reaction of the symmetric cells of HMC / CeO2 and HMC are combined into an envelope peak. Further analysis of the CV curves of the Li-S button cells of the three electrodes ( Figure 7 in b) shows that there are two reduction peaks (C1 and C2) at ~2.30 V and ~2.00 V corresponding to the reduction of S8 to lithium polysulfide Li2S x (4 ≤ x ≤ 8), and further reduction to Li2S2 / Li2S. The two split oxidation peaks (A1 and A2) at ~2.35 V correspond to the oxidation of Li2S2 / Li2S to lithium polysulfide Li2S x(4≤x≤8), further oxidized to S8. In the HMC / S, HMC / CeO2 / S and HMC / CeO2C2 / S electrodes, the reduction potential gradually shifts positively, the oxidation potential gradually shifts negatively, and the peak current size order is HMC / CeO2C2 / S>HMC / CeO2 / S>HMC / S( Figure 7 In summary, the peak current response of the HMC / CeO2C2 / S electrode is the largest and the electrochemical polarization is the smallest, which is consistent with the CV analysis results of the symmetrical battery. In order to deeply analyze the redox process of sulfur, the starting potentials of the reduction peak and oxidation peak of the CV curve are enlarged and plotted as a Tafel curve ( Figure 7 The Tafe slopes of the C1, C2, and A1 peaks in the HMC / CeO2C2 / S electrode are 51.4, 38.8, and 41.1 mV dec, respectively. -1 , which is lower than that of HMC / CeO2 / S electrode (55.7, 47.3 and 45.7 mV dec -1 ) and HMC / S electrodes (88.9, 80.2 and 47.9 mV dec -1 ), which once again confirmed the enhanced catalytic effect of HMC / CeO2C2 on the key reaction steps of sulfur redox.

[0068] Li + Diffusion behavior is also used to reveal the kinetics of sulfur reactions. 0.1-0.5 mV s -1 CV curve within the range ( Figure 8 Figures a and b) show that the redox peak current increases with the increase of scan rate, and the reduction peak potential gradually decreases, while the oxidation peak potential increases. According to the Randles-Sevcik equation, different peak currents (I p ) and the square root of the scan rate (v 0.5 ) is a linear fit such as Figure 8 In c and d. Because Li + The diffusion coefficient is positively correlated with the slope of the straight line, indicating that Li + The diffusion rate of is the largest. EIS was further used to analyze the reaction kinetics of sulfur. The EIS curves before different electrode cycles are as follows: Figure 8 As shown in Figure e, the intersection of the X-axis in the high-frequency region and the ohmic impedance (R s ), the diameter of the semicircular arc in the high-frequency region is related to the interface charge transfer impedance (R ct ), the slope of the straight line in the low frequency region is related to the lithium ion diffusion rate, and Z' is related to ω -1 / 2 The linear fit between Figure 8Among them, the corresponding equivalent circuit models and fitting results are summarized in Table 2. The ohmic impedance and charge transfer impedance of different electrodes are in the order of HMC / CeO2C2 / S < HMC / CeO2 / S < HMC / S, indicating that the electron / ion transfer in the HMC / CeO2C2 / S electrode is accelerated and the interfacial reaction kinetics is enhanced. In addition, the Li + diffusion coefficient of the HMC / CeO2C2 / S electrode is the largest, which is consistent with the analysis results of CV curves at different scanning rates, further confirming that the CeO2C2 nanoparticles embedded with oxygen-rich vacancies in the hollow carbon spheres promote the Li + diffusion.

[0069] Table 2 EIS fitting results of different electrodes before cycling

[0070]

[0071] 3. Electrochemical performance study

[0072] To systematically evaluate the improvement effect of the battery performance of the HMC / CeO2C2 electrode, the galvanostatic charge-discharge curves of different electrodes at 0.1C are shown in Fig. 9 Figure a. All three electrodes show typical two discharge platforms and one charge platform. Among them, the discharge platform at ~2.3V corresponds to the conversion of solid S8 to liquid Li2S x (4 ≤ x ≤ 8), and the discharge capacity at this stage is denoted as Q1. The discharge platform at ~2.0V corresponds to the further conversion of liquid Li2S x (4 ≤ x ≤ 8) to solid Li2S2 / Li2S, and the discharge capacity at this stage is denoted as Q2. On the contrary, the charge platform at ~2.4V corresponds to the conversion of Li2S2 / Li2S to Li2S x (4 ≤ x ≤ 8), and finally to S8, which is consistent with the results of CV analysis. The charge-discharge voltage difference at half-capacity is denoted as ΔE. As shown in Fig. 9 Figure b, compared with the HMC / S and HMC / CeO2 / S electrodes, the HMC / CeO2C2 / S electrode has the largest discharge specific capacity and Q2 / Q1 ratio, and the smallest ΔE, indicating that the HMC / CeO2C2 / S electrode has the highest sulfur utilization rate, the highest liquid-solid conversion efficiency, and the smallest voltage polarization. A pit is observed by magnifying the second platform of the discharge curve ( Fig. 9 Figure c), indicating the phase transition overpotential from liquid Li2S x (4 ≤ x ≤ 8) to solid Li2S2 / Li2S. Obviously, the HMC / CeO2C2 / S electrode has the smallest overpotential, which is related to the advantage of the oxygen-rich vacancy CeO2C2 in enhancing the sulfur redox reaction kinetics. The rate performance of different electrodes is shown in Fig. 9As shown in (d), the initial discharge capacities of the HMC / CeO2C2 / S electrode at 0.1, 0.2, 0.5, 1, 2, and 4C are 1304, 1084, 937, 843, 786, and 741 mAh·g, respectively. -1 When the current density returned to 0.1C, the discharge capacity recovered to 1072 mAh g -1 . They are higher than those of HMC / CeO2 / S electrode, and much higher than those of HMC / S electrode. In addition, the first charge-discharge curves of HMC / CeO2C2 / S and HMC / CeO2 / S electrodes at different rates ( Fig. 9 Figures e and f) show that as the current density increases, the potential difference between the charge and discharge curves gradually increases. The HMC / CeO2C2 / S electrode can provide a larger capacity and a smaller voltage difference at different current densities.

[0073] The long cycle performance of different electrodes at 0.5C current density is shown in Figure 2. Fig.10 As shown in a and b, the order of cycling stability of the three electrodes is HMC / CeO2C2 / S>HMC / CeO2 / S>HMC / S. The initial discharge capacity of HMC / CeO2 / S is 1008 mAh g -1 After 500 cycles, it still maintains 728mAh·g -1 The reversible capacity of the electrode was 0.056%, and the stable Coulombic efficiency was 97.1%, which was higher than that of HMC / CeO2 / S and HMC / S electrodes. When the sulfur surface loading increased to 4.7 mg cm -2 When HMC / CeO2C2 / S, HMC / CeO2 / S and HMC / S are cycled 500 times, the reversible areal capacities are 3.18, 2.69 and 1.73 mAh cm, respectively. -2 In summary, the HMC / CeO2C2 / S electrode has achieved significant improvements in discharge capacity, rate performance, and stability.

[0074] In summary:

[0075] The HMC / CeO2C2 composite material was successfully synthesized by hydrothermal method and annealing reduction method. The composite material has multiple advantages: large specific surface area and mesoporous carbon wall are conducive to the infiltration of sulfur and the transmission of electrons / ions; abundant mesopores and hollow cavities provide a structural basis for storing sulfur and buffering its volume expansion; CeO2C2 nanoparticles rich in oxygen vacancies grow in situ in HMC and are in close contact with carbon to form a CeO2C2 / C heterogeneous interface with good conductivity as an efficient catalyst, which is conducive to catalyzing the redox reaction of sulfur. Based on the above advantages, the HMC / CeO2C2 composite material provided by the present invention, as a sulfur-carrying material, exhibits excellent cycle stability (728mAh g after 500 cycles). -1The retention capacity) and rate performance (741mAh g -1 In addition, the HMC / CeO2C2 / S electrode exhibited a discharge capacity of 3.18 mAh cm-2 under high sulfur loading and low electrolyte conditions. -2 Therefore, the HMC / CeO2C2 composite material provided by the present invention can be used as a multifunctional sulfur-carrying material with high sulfur loading, high conductivity and high catalytic activity, and the HMC / CeO2C2 / S electrode prepared with the HMC / CeO2C2 composite material as the sulfur-carrying material can be used to develop and prepare the cathode of a high-performance Li-S battery.

[0076] The purpose of the above-mentioned embodiments is to specifically introduce the essential content of the present invention, but those skilled in the art should know that the protection scope of the present invention should not be limited to the specific embodiments.

Claims

1. A HMC / CeO2C2 composite material, the preparation method comprising the following steps: Step S1, dispersing an appropriate amount of hollow mesoporous carbon spheres HMC and an appropriate amount of cerium nitrate in an appropriate amount of deionized water, adding an appropriate amount of NaOH, and performing ultrasonic treatment for an appropriate amount of time to make the dispersion uniform; Step S2, transferring the uniformly dispersed mixture to a high-pressure reactor with a polytetrafluoroethylene liner, reacting at 95-105° C. for 9-11 hours, cooling naturally, collecting the precipitate by centrifugation, washing, and drying, and obtaining a HMC / CeO2 composite material. Step S3, placing the HMC / CeO2 composite material in a tubular furnace, heating it to 480-520°C in a flowing 4-6% H2 / Ar atmosphere, maintaining it for 2.5-3.5 hours, and cooling it naturally to obtain the HMC / CeO2C2 composite material.

2. The HMC / CeO2C2 composite material according to claim 1, characterized in that: Step S2: react at 100°C for 10 hours.

3. The HMC / CeO2C2 composite material according to claim 1, characterized in that: Step S3: Raise the temperature to 500°C at 5°C / min and maintain for 3h.

4. The HMC / CeO2C2 composite material according to claim 1, characterized in that: The atmosphere in step S3 is a 5% H2 / Ar atmosphere.

5. The HMC / CeO2C2 composite material according to claim 1, characterized in that: The preparation method of HMC comprises the following steps: First, add an appropriate amount of ammonia water to a mixed solvent of ethanol / deionized water in a volume ratio of (6-8):1, add an appropriate amount of tetrapropyl orthosilicate under stirring, and when the solution presents a milky white colloid, add an appropriate amount of resorcinol and formaldehyde solution, and stir continuously; Then, the precipitate was collected by centrifugation, washed several times with deionized water and ethanol, and dried under vacuum to obtain the HMC precursor; Finally, the HMC precursor is placed in a tube furnace, carbonized at 680-720° C. for 2.5-3.5 hours in a flowing argon atmosphere, and naturally cooled; the carbonized product is then placed in a NaOH solution to etch the SiO2 template, centrifuged, washed, and dried to obtain the product.

6. The HMC / CeO2C2 composite material according to claim 5, characterized in that: The carbonization condition of HMC precursor was 700℃ for 3h.

7. The HMC / CeO2C2 composite material according to claim 5, characterized in that: The concentration of NaOH solution for etching SiO2 template is 4M.

8. Use of the HMC / CeO2C2 composite material according to any one of claims 1 to 7 as a multifunctional sulfur-carrying material.

9. Use of the HMC / CeO2C2 composite material according to any one of claims 1 to 7 as a sulfur-carrying material for preparing an HMC / CeO2C2 / S electrode.

10. Use of the HMC / CeO2C2 / S electrode according to claim 9 for preparing a cathode of a lithium-sulfur battery.